Can Viewing Nature Through Windows Improve Isolated Living? A Pathway Analysis on Chinese Male Prisoners During the COVID-19 Epidemic - Li, Hansen; Zhang, Xing; You, Chengming; Chen, Xin; Cao, Yang; Zhang, Guodong (Frontiers in Psychiatry, 2021)
Nature exposure is known to promote life satisfaction and well-being, and exposure via the window was reported to possibly benefit isolated population. However, the mechanism for indoor nature exposure is unclear, and whether the indirect exposure is also effective for prisoners, the extremely isolated population, is still unknown. Therefore, an investigation was conducted on 326 male prisoners from three prisons in southwest China. Psychological variables including depression, anxiety, loneliness, distress tolerance, life satisfaction, and well-being were measured using Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), short-form UCLA Loneliness Scale (ULS-6), Distress Tolerance Scale (DTS), Satisfaction with Life Scale (SWLS), and 5-item World Health Organization Well-Being Index (WHO-5) respectively. Structural equation modeling was employed to identify the pathways from visibility of nature via window to prisoners’ life satisfaction and well-being. Results demonstrated that visibility of nature promoted frequency and duration of viewing nature via window. The frequency exerted a direct effect on well-being, but the duration was found ineffective on any variables. The visibility of nature via window enhanced life satisfaction mainly via a direct effect meanwhile enhanced well-being via multiple indirect pathways. Regarding the main significant indirect pathways, the increased life satisfaction and well-being were driven by the increased visibility of nature through increasing distress tolerance that directly decreased mental health problems meanwhile indirectly decreased them via decreasing loneliness. Our findings suggest that nature exposure via window is effective to enhance prisoners’ life satisfaction and well-being, and distress tolerance could be improved by window view of nature, which may play an important mediatory role in coping with mental health problems in nature exposure. The community and prison construction may need to consider the visibility of neighborhood greening to promote indirect nature exposure for the isolated population.